Alleviating Poverty through Micro Finance: Nigerias Experience - Lawanson, Olukemi I (Asian Journal of Economic Modelling, 2016)
Poverty is a global phenomenon, especially in the less developed countries like Nigeria and it has aroused the concern of people all over the world, including individuals, Non-Governmental Organizations (NGO’s), Multilateral Institutions such as the World Bank and the United Nations Development Programme (UNDP), as well as national governments. Microfinance is still a relatively new phenomenon in Nigeria as it was just employed as a strategy for poverty reduction in December 2005. The first Microfinance Bank can be traced back to 1976, when Muhammad Yunus set up the Grameen Bank, as an experiment, on the outskirts of Chittangong University campus in the village of Jobra, Bangladesh. Since the Microfinance policy was put in place in December 2005, the effect has rarely been felt; it hasn’t had the adequate trickle-down effect on the Nigerian citizenry because the gap between the rich and the poor is still on the increase. Poverty is a critical phenomenon that calls for an urgent attention and solution all over the world, especially in the underdeveloped nations of the world where it has eaten deep into the lives of many. The need to alleviate poverty arises in order to enhance the quality of life through the creation of favorable standards of living by effective production and distribution of consumer goods and services. This study seeks to determine the effect that Microfinance Institutions have had on reduction, or alleviation of poverty in Nigeria.